State of the art in technologies of the biogas production increasing during methane digestion of sewage sludge = Przegląd technologii intensyfikacji produkcji biogazu podczas fermentacji metanowej osadów ściekowych - Wiśniowska, Ewa; Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
At present many WWTPs are focused on increasing quantity of biogas generated during sewage sludge processing. Various disintegration methods can be used for this purpose ? thermal heating, ultrasonic disintegration, chemical treatment.
Keywords: sewage sludge; biogas; methane digestion; disintegration; osady ściekowe; biogaz; fermentacja metanowa; dezintegracja